2015
DOI: 10.5713/ajas.14.0592
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Wet and Dried Distillers Grains on <i>In vitro</i> Ruminal Fermentation and Effects of Dietary Wet Distillers Grains on Performance of Hanwoo Steers

Abstract: Two experiments were conducted to evaluate the nutrient composition, in vitro dry matter disappearance (IVDMD) and organic matter disappearance (IVOMD) of three kinds of distillers grains (DG); i) wet distillers grains (WDG, KRW 25/kg), ii) dried distillers grains (DDG, KRW 280/kg), iii) dried distillers grains with solubles (DDGS, KRW 270/kg) produced from tapioca 70% and rice 30%, and to evaluate dietary effects of WDG on the performance of Hanwoo steers. In Exp. 1, twelve-WDG, four-DDG and one-DDGS were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
13
1
Order By: Relevance
“…In this study, CP concentrations of WDG from different sampling dates ranged from 19.6% to 30.3% (DM basis), and average CP concentrations of WDG were 24.8% (DM basis). Kim et al (2015) reported that CP concentrations of WDG (tapioca and rice, 7:3) from seven ethanol plant ranged from 26.5% to 40.4% (DM basis), thus showed higher CP concentrations than our study. The concentration of CP for WDG depends on the proportion and type of grain sources.…”
Section: Resultscontrasting
confidence: 66%
See 3 more Smart Citations
“…In this study, CP concentrations of WDG from different sampling dates ranged from 19.6% to 30.3% (DM basis), and average CP concentrations of WDG were 24.8% (DM basis). Kim et al (2015) reported that CP concentrations of WDG (tapioca and rice, 7:3) from seven ethanol plant ranged from 26.5% to 40.4% (DM basis), thus showed higher CP concentrations than our study. The concentration of CP for WDG depends on the proportion and type of grain sources.…”
Section: Resultscontrasting
confidence: 66%
“…In addition, there were no data available about the in vitro ammonia concentrations and pH of WDG itself. WDG can be a useful protein source for ruminants ( Kim et al, 2015 ), thus in vitro ammonia concentrations of WDG itself may be useful data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are high in crude protein (CP), fatty acids, tannins, and vitamins [ 1 ] and therefore have been great potential for utilization as animal feed. For example, corn distillers dried grain with soluble diets have replaced up to 40 % of total feed as a protein source in the United States [ 2 ] and the use of wet distillers grain (WDG) up to 10 % in total mixed ration (TMR) did not show any negative effect on the performance of Hanwoo steers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%